Hey there!
To start, first simplify your expression by distributing your values to the equation inside the parenthesis:
5(-3x - 2) - (x - 3) = -4(4x + 5) + 13
(5*-3x)+(5*-2)-x-3=(-4+4x)+(-4*5)+13
-15x-10-x-3=-16x-20+13
Now, combine your like terms, or terms that are raised to the same power and have the same variables that are also raised to the same power:
-15x-10-x-3=-16x-20+13
(-15x-x)+(-10-3)=-16x+(-20+13)
-16x-7=-16x-7
Because your equation is set equal to itself, your answer would be all real solutions as any real number can be plugged into the variable and have a valid answer.
Hope this helps and have a wonderful day! :)